(3YeGQI GdMfjI hRNGQagG GdafjI aj GdcfGFS GdTQbjI MJi fgGjI GdbQf GdSGHY GdejdGOj (B:s c - (3,eGQi KGHJ EHQGgje fUjas; (3efi LHQ YHO GdfHj MSjfs (2025)
(3jJfGhd GdHMK ehVhY YeGQI GdMfjI hRNGQagG GdafjI aj GdcfGFS GdTQbjI MJi fgGjI GdbQf GdSGHY GdejdGOi JWHjkbG Ydi GdcfGFS GdeUQjI hGdShQjI hjfbSe GdHMK Edi LRFjf(B: (3GdLRA GdChd JegjO hCQHYI aUhd hNGJeI hedGMb hLGAJ Ydi QCSge LejkYG GdebOeI GdJj JYQV CgejI GdHMK hCSHGH GNJjGQ GdehVhY HGdEVGaI Edi GdOQGSGJ GdSGHbI(B.(3GdaUd GdChd jJfGhd ChdkG(B: (3eSejGJ GdMfjI GdeNJdaI, KGfkjG(B: (3YeGQI GdMfjI aj eUQ hShQjG HCTcGdgG GdeNJdaI,GdaUd GdKGfj jJfGhd OQGSI hUajI dRNGQa GdMfGjG aj eUQ WHkbG dJhRjY GdefGXQ Ydi GdMfjI,GdaUd GdKGdK jJfGhd OQGSI hUajI dRNGQa GdMfGjG aj ShQjG ddLOQGjGJ hGdCQVjGJ(B.(3GdaUd GdQGHY jJfGhd OQGSI JMdjdjI dCge GdYfGUQ GdeYeGQjI hGdafjI GdJj XgQJ aj GdMfGjG(B.(3Ke JCJj GdNGJeI(B.s
The research is divided into two parts .Part one:The introduction: It discusses the naming of ancient Syria, its geographical divisions, and Christianity in Syria during the early Byzantine period, followed by architecture and art in Syria.Chapter One: Firstly, it addresses the different names of the apse. Secondly, it discusses the architecture of the apse in Egypt and Syria in.Chapter Two: It covers a descriptive study of the decorative motifs of the apses in Egypt based on the arrangement of the scenes on the apse.Chapter Three: It presents a descriptive study of the decorative motifs of the apses in Syria regarding the ceilings and floors.Chapter Four: It focuses on an analytical study of the most crucial architectural and artistic elements.Part two: An index of illustrations.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2025. s
(3HHdjhLQGajG(B: (3UaMGJ (B220-237.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdcfGFS GdTQbjIs -- (3YeGQIs; (3GdMfjI s -- (3eUQs -- (3ShQjG s